Inclusive discourse in the coverage of blasphemy cases in Indonesian online media: A Foucauldian perspective - Pribadi, Farid; Khotimah, Khusnul; Surokim, Surokim; Amil, Ahmad Jami'ul (Center for Sociological Studies and Community Developmen, 2025)
This study employs Foucauldian discourse analysis to investigate how three major Indonesian online media outlets—Detik.com, Tribunnews.com, and Kompas.com—constructed public discourse surrounding Pastor Gilbert’s 2024 blasphemy case. By analyzing coverage from April to July 2024, the research uncovers how media narratives reinforced the dominance of the Islamic majority while marginalizing minority perspectives in Indonesia’s pluralistic society. All three outlets functioned as panoptic instruments, aligning with state-religious authorities such as the MUI, DMI, and Jusuf Kalla to define “truth” and shape acceptable discourse. Detik.com portrayed Gilbert’s apology as a resolution aligned with majority sensibilities; Tribunnews.com privileged Islamic leaders' critiques while minimizing Gilbert’s own explanations; Kompas.com deployed selective “evidence” to label him a blasphemer, disregarding theological nuance. Across the platforms, epistemic violence was evident: Gilbert’s voice was delegitimized, reconciliation was conditioned by dominant norms, and dissent was monitored through harmony-oriented rhetoric. The media’s collaboration with biopolitical forces—police investigations and politico-religious framing—deepened structural hierarchies and exemplified Foucault’s notion of truth as a product of power. While each outlet employed distinct strategies, all participated in disciplining discourse and excluding dissenting voices. This study calls for ethical reflection on the media’s role in shaping inclusive narratives and promoting justice in a multicultural nation.